Transformasi Zakat Digital dan Pembudayaan Mustahik di Era Kontemporer - Afrizal; Allan Harris; M Abdullah Umar (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
This study aims to analyze the trend of digital zakat in Indonesia and its impact on the empowerment of mustahik in the contemporary era. Specifically, it explores the development dynamics of digital zakat, assesses the influence of technological innovation on zakat collection and distribution patterns, and evaluates its effectiveness in empowering mustahik and improving their sustainable socio-economic welfare. This research employs a qualitative method with a literature study approach. Data were collected through primary and secondary documents, including scientific publications, official reports from the National Amil Zakat Agency (BAZNAS), regulations of the Ministry of Religious Affairs, journal articles, and credible online sources related to digital zakat practices. The analysis uses content analysis to identify, select, and evaluate information regarding collection mechanisms, distribution systems, technological innovations, and socio-economic impacts on mustahik. The findings indicate that advancements in information technology have driven significant transformation in the digital zakat system, enabling more systematic and transparent collection and distribution through digital networks. While digitalization improves efficiency, major challenges remain, including unequal digital literacy between muzakki and mustahik and limited technological access in remote areas, which require mitigation strategies and capacity strengthening. Additionally, monitoring and evaluation are essential to ensure that zakat funds are properly distributed and produce tangible impacts. This study also highlights that digital zakat optimizes zakat potential, promotes modern philanthropic practices, and supports the achievement of the Sustainable Development Goals (SDGs), particularly poverty alleviation and reducing social inequality. Thus, digital zakat serves as a strategic instrument for sustainable social welfare.